2017
DOI: 10.46281/ijfb.v1i1.82
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Role of Commercial Banks in Financing Small and Medium Scale Enterprises (SMEs): Evidence from Nigeria

Abstract: In this study an attempt was made to evaluate the role of commercial banks in financing small and medium scale enterprises in Nigeria. There is absolutely no doubt that small and medium scale enterprises play a pivotal role and contributes tremendously to the economic growth and development of many developing economy including Nigeria, but survival of Small and medium scale enterprises is often hampered by access to finance which key players were making attempt to solve. The objective of this study is to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…The known sources include equity share capital, reserves and surplus, preference share capital, debts, debentures, and others, such as long term sources of finance (Okeke, 2019). SMEs have limited sources of finance because according to the nature of their businesses, they can only use owner savings, loans from family and friends, and debts sources, but equity financing is not attractive to them as it is too demanding and compliance costs are high (Gololo, 2017). The limited sources of finance for SMEs compromises their growth aspirations (Afande et al, 2015;Atiase et al, 2018).…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…The known sources include equity share capital, reserves and surplus, preference share capital, debts, debentures, and others, such as long term sources of finance (Okeke, 2019). SMEs have limited sources of finance because according to the nature of their businesses, they can only use owner savings, loans from family and friends, and debts sources, but equity financing is not attractive to them as it is too demanding and compliance costs are high (Gololo, 2017). The limited sources of finance for SMEs compromises their growth aspirations (Afande et al, 2015;Atiase et al, 2018).…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…The result support the a-priori expectation and the findings of the study corroborates with the study of Oluitan (2014), Ayuba and Zubairu (2015), Dalhat and Hassan (2016) and Abosede et al (2017) where they found significant positive relationship between access to credit and SMEs performance. However, Imafidon and Itoya (2014), Ubesie et al (2017), Owolabi and Nasiru (2017) and Ibrahim (2017) reported negative significant relationship between access to credit and the performance of SMEs. This might be due to geographical, population and sample size or construct of the study peculiarities.…”
Section: Discussion Of Findingsmentioning
confidence: 98%
“…Globally, a lot has been said and written on the role of SMEs in the advancement of any economy. In the same token, government in Nigeria has focused on SMEs by formulating policies aimed at enhancing the performance and growth of the sector (Eniola & Entebang, 2015;Ibrahim, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Supply lending theory was postulated by Ibrahim (2017). The stance of the theory is that , the presence of financial institutions and their provision of financial resources and services in before demand for such resources enhances efficient allocation of resources from surplus units to deficit units.…”
Section: Supply Lending Theorymentioning
confidence: 99%
“…Historical evidences showed that before the end of 19th century, SMEs served as the pillar of economies in Europe (Aremu & Adeyemi 2011). However, the advent of Industrial revolution, which brought about mass production, reduced the contribution of SMEs to economic growth in comparison to large enterprises (Ibrahim, 2017). The contribution of SMEs to Gross Domestic Product ( GDP) in Nigeria in the last five years is forty-eight percent (According to Bureau of Statistics, 2022).…”
Section: Introductionmentioning
confidence: 99%